Enterococcal bloodstream infections in critically ill patients with COVID-19: a case series. (1st January 2021) - Giacobbe, Daniele Roberto; Labate, Laura; Tutino, Stefania; Baldi, Federico; Russo, Chiara; Robba, Chiara; Ball, Lorenzo; Dettori, Silvia; Marchese, Anna; Dentone, Chiara; Magnasco, Laura; Crea, Francesca; et al.
Abstract: Background: An unexpected high prevalence of enterococcal bloodstream infection (BSI) has been observed in critically ill patients with COVID-19 in the intensive care unit (ICU). Materials and methods: The primary objective was to describe the characteristics of ICU-acquired enterococcal BSI in critically ill patients with COVID-19. A secondary objective was to exploratorily assess the predictors of 30-day mortality in critically ill COVID-19 patients with ICU-acquired enterococcal BSI. Results: During the study period, 223 patients with COVID-19 were admitted to COVID-19-dedicated ICUs in our centre. Overall, 51 episodes of enterococcal BSI, occurring in 43 patients, were registered. 29 (56.9%) and 22 (43.1%) BSI were caused by Enterococcus faecalis and Enterococcus faecium, respectively. The cumulative incidence of ICU-acquired enterococcal BSI was of 229 episodes per 1000 ICU admissions (95% mid-p confidence interval [CI] 172–298). Most patients received an empirical therapy with at least one agent showing in vitro activity against the blood isolate (38/43, 88%). The crude 30-day mortality was 42% (18/43) and 57% (4/7) in the entire series and in patients with vancomycin-resistant E. faecium BSI, respectively. The sequential organ failure assessment (SOFA) score showed an independent association with increased mortality (odds ratio 1.32 per one-point increase, with 95% confidence interval 1.04–1.66, p = .021). Conclusions: The cumulative incidence of enterococcal BSI is high in critically ill patients with COVID-19. Our results suggest a crucial role of the severity of the acute clinical conditions, to which both the underlying viral pneumonia and the enterococcal BSI may contribute, in majorly influencing the outcome. KEY MESSAGES: The cumulative incidence of enterococcal BSI is high in critically ill patients with COVID-19. The crude 30-day mortality of enterococcal BSI in critically ill patients with COVID-19 may be higher than 40%. There could be a crucial role of the severity of the acute clinical conditions, to which both the underlying viral pneumonia and the enterococcal BSI may contribute, in majorly influencing the outcome.